Orthogonal Projections Based on Hyperbolic and Spherical n-Simplex - Murat Savas; Baki Karliga; Atakan T. Yakut (Advances in Mathematical Physics)
Orthogonal projection along a geodesic to the chosen k-plane is introduced using edge and Gram matrix of an n-simplex in hyperbolic or spherical n-space. The distance from a point to k-plane is obtained by the orthogonal projection. It is also given the perpendicular foot from a point to k-plane of hyperbolic and spherical n-space.